Unmanned aerial vehicle with multiple rotor wings - GUO ZHANGYONG (2016)
The utility model relates to an aerospace vehicle field, through providing an unmanned aerial vehicle with multiple rotor wings, this unmanned aerial vehicle includes that fuselage body, horn, screw, drive arrangement and setting are at this internal power storage device of fuselage, the horn, with fuselage body fixed connection and symmetry set up for bear the screw, drive arrangement installs the horn tip that is just corresponding at the screw for the rotation of drive screw, drive arrangement still includes fuel engine and motor generator, wherein, fuel engine's quantity is at least two, and sets up for fuselage body symmetry. Still be equipped with the generator in addition, can become the electric energy with oil -fired energy conversion, provide electric energy, energy saving for motor generator. This unmanned aerial vehicle with multiple rotor wings sets up fuel engine through the symmetry, can solve the structure complicacy and the inefficiency scheduling problem that aim at solving current hybrid un